(untitled) (Open Herald: Periodical of Methodical Research, 2026)
This article examines the history of formation, stages of development, and current state of terminology in the field of road construction on the basis of comparative linguistics methods. A lexical-semantic, morphological, and etymological analysis of terms was carried out on the material of the Uzbek, Russian, and English languages. In the course of the study, the ways in which specialized terminology enters the national terminological system, the ratio between borrowed and native terms, as well as the problems of standardization were reviewed